Pengaruh Pemberian Pelatihan Dan Motivasi Terhadap Kinerja Karyawan Bagian Produksi di PT. Surabaya Mekabox Paper Mill, Gresik - Widji Nurhayati; Harsono Teguh Santoso; Achmad Daengs GS; Sugiharto Sugiharto; Bambang Karnain (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
According to Maslow (in Greenberg and Baron, 1997:145), defines that every human being has many biological needs (Phsycological needs), safety needs (safety needs), social needs (social needs), esteem needs (esteem needs), and self-actualization needs. With these work needs, employees also have both material and non-material needs, for example the need for clothing, food, shelter, the need to feel accepted by others where they live and work, the need to live to be able to achieve, the need for security while working, and a feeling of security concerning their future, and many other needs that can be obtained from the place where they work. With the many human needs as employees who work in a company, according to Widyarto Adi PS (Human Resource Management article number 107/ September - October 1996) Companies must be proactive and responsible in responding to all changes that occur and how to overcome the impact of changes that occur on the HR management function. The change in the role of HR is caused by the pressure caused by developments that occur everywhere, in the social, economic, cultural, technological, environmental, and other fields. In this economic recession, all companies are competing fiercely to survive and even then they need help from the employees who work in them. Along with that, technological progress is increasingly rapid and unpredictable, so that it requires everyone involved in the company to be able to continue to follow these developments by learning new things so as not to be left behind. Therefore, the company must help employees to realize this by providing appropriate training.